Inclusive Theology and Religious Pluralism: A Critical Analysis of Major Thinkers - Hasfiana, Hasfiana; Muh. Natsir Siola; Abdullah, Abdullah (al-Afkar, Journal For Islamic Studies, 2026)
Debates on the theology of religions, particularly between inclusive theology and religious pluralism, have become a significant issue in the context of Indonesia’s plural society. This article aims to critically analyze the concepts of inclusive theology and religious pluralism and examine their relevance for fostering interreligious relations in Indonesia. Employing a qualitative approach based on library research, this study explores the ideas of key figures such as Nurcholish Madjid and John Hick, as well as Indonesian Muslim responses to religious pluralism. The findings indicate that inclusive theology offers a middle ground that enables Muslims to maintain strong theological commitments while remaining open to dialogue and cooperation with followers of other religions. In contrast, religious pluralism understood in a theological sense namely, the notion that all religions are equally true and lead to the same salvation has been subject to serious methodological and theological criticism, as it is considered incompatible with the principle of tawhid in Islam. In the Indonesian context, this debate is further complicated by the Indonesian Council of Ulama’s (MUI) fatwa on religious pluralism and the emergence of religious moderation as a paradigm emphasizing the principle of wasathiyyah (the middle path). This article concludes that an Islamic wasathiyyah approach, which distinguishes between plurality as a sociological fact and pluralism as a theological ideology, provides the most contextual framework for managing religious diversity in a dialogical, just, and peaceful manner without undermining Islamic theological integrity.